2015
DOI: 10.3382/ps/pev223
|View full text |Cite
|
Sign up to set email alerts
|

Methods for assessment of keel bone damage in poultry

Abstract: Keel bone damage (KBD) is a critical issue facing the laying hen industry today as a result of the likely pain leading to compromised welfare and the potential for reduced productivity. Recent reports suggest that damage, while highly variable and likely dependent on a host of factors, extends to all systems (including battery cages, furnished cages, and non-cage systems), genetic lines, and management styles. Despite the extent of the problem, the research community remains uncertain as to the causes and infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(116 citation statements)
references
References 40 publications
6
107
2
1
Order By: Relevance
“…Previous studies have suggested less frequent occurrence (5,(20)(21)(22)(23)(24) with typically 50-80% of surveyed hens manifesting keel fractures by the end of lay using palpation or dissection. As a potential explanation for the relatively higher frequency seen in the current study, our protocol allowed for recent, healed, and minor fractures to be diagnosed (7,9) which could be missed with palpation and/or dissection. Alternatively, flock and facility differences could have played a role as our observations where conducted within a single barn, though previous efforts in the same barn with assessment by dissection also found a lower frequency of fracture (25).…”
Section: Fracture Incidencementioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have suggested less frequent occurrence (5,(20)(21)(22)(23)(24) with typically 50-80% of surveyed hens manifesting keel fractures by the end of lay using palpation or dissection. As a potential explanation for the relatively higher frequency seen in the current study, our protocol allowed for recent, healed, and minor fractures to be diagnosed (7,9) which could be missed with palpation and/or dissection. Alternatively, flock and facility differences could have played a role as our observations where conducted within a single barn, though previous efforts in the same barn with assessment by dissection also found a lower frequency of fracture (25).…”
Section: Fracture Incidencementioning
confidence: 97%
“…The most common method for evaluating whether laying hens have keel bone fractures (KBF) is palpation, a relatively simple and low-cost method that allows for longitudinal observations. Despite these benefits, palpation requires assessors to undergo training and evaluation to ensure reliable and accurate results (4,7). Even with superior training, it is likely that a large percentage of fractures will be missed due to a variety of reasons including: fissures, inability to detect fractures on the dorsal aspect of the keel, or damage hidden by the large breast muscle group.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of deviated keel bones, being defined as "bone [s] with an abnormally shaped structure that has not resulted from a fracture but contains section(s) that vary from a theoretically perfect 2-dimensional straight plane in either the transverse or sagittal planes. Additionally, indentations along the ventral surface can also be classified as a deviation" (11), can reach up to 82% (12,13). Age (4,5,(14)(15)(16)(17)(18), different housing systems (4,7,19), nutrition (20)(21)(22), and genetic background (5, 17-19, 23, 24) have been shown to influence KBD.…”
Section: Introductionmentioning
confidence: 99%
“…The impact on production parameters appear to be less documented, however, increased feed conversion and reduced laying and egg quality have been reported [15][16][17][18]20]. In addition, several studies have focused on diagnosing the condition, mainly, by palpation techniques and radiographs [4,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%